Analisis Variabel-Variabel Yang Memengaruhi Keputusan Pembelian Konsumen Di Pameran Sepatu Jakarta Sneakers Day - Rizki Fajar, Mohammad; Suhud, Usep; Febrilia, Ika (CV. Lafadz Jaya, 2023)
This study aims to analyze the influence of digital marketing, viral marketing, brand prestige, brand loyalty, and lifestyle variables on purchasing decisions for local brand sneakers at Jakarta Sneakers Day. The method of data collection is using the survey method with likert type purposive sampling. The object of this research is 227 respondents who were visitors to Jakarta Sneakers Day in Jabodetabek. This research used SPSS software version 25 and SEM (Structural Equation Modelling) AMOS version 25 for data analysis. The result of this study suggest: 1) digital marketing has a positive and significant effect on purchasing decisions, (2) viral marketing has a positive and significant effect on purchasing decisions, (3) brand prestige has a negative and insignificant effect on purchasing decisions. (4) brand loyalty has a positive and significant effect on purchasing decisions. (5) lifestyle has a positive and significant.